In vivo immune responses to Candida albicans modified by treatment with recombinant murine gamma interferon. - Garner, R. E. (1989)
The immunologic effects of in vivo administration of recombinant murine gamma interferon (rMuIFN-gamma) were determined in a murine model of candidiasis. Naive mice were given graded doses of rMuIFN-gamma and then challenged intravenously with Candida albicans. Increased morbidity and mortality were noted in four different strains of mice, viz., BALB/c, A/J, Swiss Webster, and CBA/J, providing the mice had not been immunized with C. albicans before challenge. Quantitative culture of selected organs of Swiss Webster and CBA/J mice surviving treatment with rMuIFN-gamma revealed elevated numbers of C. albicans cells, particularly in the kidneys, but also in the liver, lungs, and spleen. The lungs, livers, and spleen of female CBA/J mice were more protected from increased multiplication of the fungus than were those of males of the same species or female Swiss Webster mice. On the basis of these initial findings, the effect of treatment with 5,000 U of rMuIFN-gamma on immune responses in a gastrointestinal model of candidiasis was determined. CBA/J mice that had been colonized with C. albicans as infants were boosted with a cutaneous inoculation of the fungus when 6 to 10 weeks old; development of delayed hypersensitivity (DH), antibodies, and protective responses was assayed at intervals thereafter. Daily treatment with rMuIFN-gamma (beginning 1 day before cutaneous inoculation) suppressed weak immune responses but had little effect on responses which were strong. For example, DH and anti-C. albicans antibody production were suppressed in animals colonized with C. albicans but not boosted by cutaneous inoculation, and DH was suppressed in uncolonized animals that had been inoculated once cutaneously with the fungus as well. There was no rMuIFN-gamma-induced suppressive effect of DH in mice which had been stimulated maximally with C. albicans, i.e., colonized animals that had been boosted cutaneously with the organisms. Collectively, these data indicate that naive mice or mice with minimal levels of anti-C. albicans sensitivity, females somewhat more so than males, were sensitive to suppressive effects of in vivo treatment with rMuIFN-gamma when challenged with C. albicans. In contrast, under conditions similar to those of humans, in whom underlying immunity to C. albicans is usually present, suppression of host responses to C. albicans was not observed in immunized mice in response to treatment with rMuIFN-gamma.